2017
DOI: 10.1590/1980-5497201700040015
|View full text |Cite
|
Sign up to set email alerts
|

Análise espaço-temporal da doença de Chagas e seus fatores de risco ambientais e demográficos no município de Barcarena, Pará, Brasil

Abstract: Different relationships among the variables studied and the occurrence of the disease in the municipality were observed. The technologies used were satisfactory to construct the disease epidemiological scenarios.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
5

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 36 publications
0
12
0
5
Order By: Relevance
“…Therefore, as these are low-educated and low-income populations, these factors stand in the way of optimized clinical treatment and control of disease progression, contributing to the fact that CD remains a risk factor for negative outcomes in HF patients. 18,19 Martinelli et al 20 conducted a study of 116 patients with CD who implanted ICD for secondary prevention, with a lower mortality rate than our study (26.7% deaths over a mean follow-up of 45 months, 7.1% annual mortality rate). The higher mortality seen in our population can be explained by the severity profile of our patients, with higher prevalence of NYHA class III or IV and lower LVEF.…”
Section: Resultsmentioning
confidence: 46%
See 1 more Smart Citation
“…Therefore, as these are low-educated and low-income populations, these factors stand in the way of optimized clinical treatment and control of disease progression, contributing to the fact that CD remains a risk factor for negative outcomes in HF patients. 18,19 Martinelli et al 20 conducted a study of 116 patients with CD who implanted ICD for secondary prevention, with a lower mortality rate than our study (26.7% deaths over a mean follow-up of 45 months, 7.1% annual mortality rate). The higher mortality seen in our population can be explained by the severity profile of our patients, with higher prevalence of NYHA class III or IV and lower LVEF.…”
Section: Resultsmentioning
confidence: 46%
“…Another possible cause for our results is the social profile of these patients with CD, since a considerable part of these patients have low family income and low education. Therefore, as these are low‐educated and low‐income populations, these factors stand in the way of optimized clinical treatment and control of disease progression, contributing to the fact that CD remains a risk factor for negative outcomes in HF patients …”
Section: Discussionmentioning
confidence: 99%
“…The age group that is most frequently affected in this study corroborates with that in other studies. This finding indicates that the risk of CD infection increases during the most productive age of the individual and in those living in rural areas; during this period, the individual's most common activities were plant extraction and farming 15,16 .…”
Section: Discussionmentioning
confidence: 91%
“…Deforestation carried out in the broad and unrestricted way in tropical forests is far from being just a moral problem―it is about to become a public health problem [ 35 ]. Studies have already shown that deforestation can lead to increased transmission of malaria [ 36 ], hantavirus [ 22 ], visceral leishmaniasis [ 37 ], and Chagas disease [ 38 ], to name just a few known examples. In the present study, we obtained evidence that accumulated deforestation between 30 and 70% and the fragmentation of the remaining forest equal to or above 80 m/ha, on the municipality scale, are associated with the occurrence of YF in Brazil, 2014–2019.…”
Section: Discussionmentioning
confidence: 99%